Impact of radiation therapy on the heart - Siti Utami Dewi; Allenidekania Allenidekania (Media Keperawatan Indonesia, 2022)
Radiation therapy is the most important part of a modality in the management of patients with malignancy. The incidence of heart disease caused by radiation has increased in recent decades, due to the increased survival rate of patients with malignancies in the chest area receiving radiation therapy. Purpose To determine the impact on the heart due to radiation therapy in cancer patients. This study is a literature review, articles were collected using Google Scholar, ScienceDirect, and PubMed databases with the keywords radiation, heart disease, cancer patients, and radiotherapy. Inclusion criteria included articles published from 2013-2022. Based on a review of 10 articles discussing the effect of radiation therapy on the heart. Some cardiovascular complications due to radiation therapy can affect the pericardial, myocardial, vascular, heart valves, and conduction disturbances. Radiation-induced heart disease is a growing concern because it is associated with increased survival in cancer patients. It is important for clinicians to understand the impact of radiation therapy on the heart for the purposes of education, consideration of therapy and dose, monitoring of therapy, and early detection.